Clinical results of intensity-modulated radiation therapy (IMRT) for tumors of the head and neck region - Odrazka, K; Petera, J; Zouhar, M; Vosmik, M; Vaculikova, M; Dolezel, M; Kohlova, T; Filip, S; Ceral, J; Hobza, V; Rehak, S; Dolezal, J (Neoplasma, 2005)
Intensity-modulated radiation therapy (IMRT) is an advanced form of the three-dimensional conformal radiation therapy (3D-CRT). Highly conformal dose distribution is the basic feature of IMRT. The head and neck region is suitable for this new technology since the primary tumor is often surrounded by several critical structures. IMRT offers the ability of dose escalation due to steep dose gradient towards healthy tissues. In this review, clinical results of IMRT in several head and neck sites are presented, including intracranial tumors. Parotid-sparing strategies and patterns of local-regional failures are analyzed. The possibilities of irradiation of recurrent malignancies are mentioned. In perspective, the potential of IMRT should be explored in conjunction with altered fractionation regimens, including simultaneous integrated boost (SIB). Particularly, studies with dose escalation are desirable.
Keywords: výsledek terapie; nádory mozku; konformní radioterapie; nádory hlavy a krku; Brain Neoplasms; Head and Neck Neoplasms; Dose Fractionation, Radiation; Humans; Radiotherapy, Conformal; frakcionace dávky záření; Treatment Outcome; lidé